2014
DOI: 10.1210/jc.2013-4417
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Enzyme Supplementation Improves the Incretin Hormone Response and Attenuates Postprandial Glycemia in Adolescents With Cystic Fibrosis: A Randomized Crossover Trial

Abstract: In young people with pancreatic insufficient CF, PERT markedly attenuates postprandial hyperglycemia by slowing gastric emptying and augmenting incretin hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 40 publications
3
64
0
1
Order By: Relevance
“…Pancreatic enzyme supplementation slowed gastric emptying and markedly decreased the postprandial glycaemic excursion ( Fig.1-2) [41]. We recently reported the same phenomenon in a study of 14 paediatric CF patients (Fig.3) [45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 52%
See 4 more Smart Citations
“…Pancreatic enzyme supplementation slowed gastric emptying and markedly decreased the postprandial glycaemic excursion ( Fig.1-2) [41]. We recently reported the same phenomenon in a study of 14 paediatric CF patients (Fig.3) [45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 52%
“…Despite the potential importance of abnormal gastric emptying in CF patients, only a limited number of studies have evaluated gastric emptying in this population [33,[41][42][43][44][45], with inconsistent results, attributable to differences in subject characteristics, meal composition, use of pancreatic enzymes and the method used to measure gastric emptying. Studies have reported abnormally rapid [41,42] or delayed [44] emptying, or no difference from controls [33,43,45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 99%
See 3 more Smart Citations